Application of Hazard Analysis and Critical Control Points (HACCP) of Frozen Tuna Loin at PT. Arta Mina Jaya, Wakatobi Regency - Kasrun, La Ode; Karimuna, La; Syukri, Muhammad (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aimed was to analyze the application levels of critical control points of HACCP in Frozen loin tuna processing in identifying hazards and preventing the dangers found in loin at PT. Arta Mina Jaya. This research was descriptive with the method used as the survey method using a questionnaire of the selected respondents. The survey method was carried out by following the entire flow process of handling frozen tuna loin from receiving raw materials, washing, head cutting, skin removal, tidying up, CO injection, loin cooling, final control and size determination, vacuuming, freezing, second weighing, packaging and labeling, metal inspection, cold storage up to transportation. The survey method was carried out by following the entire flow process of handling frozen tuna loin from receiving raw materials to transportation. This study also used the decision tree method to identify critical control points. Next was the identification of critical control points by looking at the critical temperature limit <200C, the temperature limit of the production room <350C, the danger, 100 ppm metal and identify CCP. The results of the study indicated that the process of implementing HACCP levels at PT. Arta Mina Jaya was better in the application of HACCP.Â